A ‘Missed’ Diagnosed Case of Christ-Siemens-Touraine Syndrome - Narayan, Shambhavi (Journal of Nepal Paediatric Society, 2017)
Christ-Siemens-Touraine syndrome also known as Anhidrotic ectodermal dysplasia, is a rare genetic disorder, occurring in 1-100,000 live male births. A two year old male child with classical signs and symptoms of the disease, affecting skin, hairs, nails and teeth, misdiagnosed initially as a case of seborrhic dermatitis, and later as tuberculosis, is described here. Treatment includes counselling the family, skin care, avoiding high ambient temperature, and prosthodontic measures. Diagnosis as early as possible, based mainly on clinical features can prevent mortality due to hyperpyrexia and respiratory infections. Beyond early childhood, life expectancy is normal to slightly reduced.